FRI0296 WHI-131, JAK3 Inhibitor, Inhibits Osteoclastogenesis and Promotes Osteoblastogenesis. (9th June 2015) - Cheon, Y.-H.; Kim, J.-Y.; Oh, J.-M.; Lee, W.-S.; Yoo, W.-H.; Lee, M.-S.; Lee, C.-H.
Abstract : Background: WHI-131/JANEX-1 (4-(4'Hydroxyphenyl)-amino-6, 7-dimethoxyquinazoline), quinazoline-type small molecule compound is well known a JAK3 inhibitor that demonstrated as potent therapeutic agent about anti-inflammatory, anti-cancer, and anti-leukemia in several animal models. However, has not been fully investigated for regulatory effects on osteoblast and osteoclast activity by WHI-131. Objectives: Therefore, in this study, we examined the effects of WHI-131 in bone remodeling during osteoblast and osteoclast differentiation. Results: WHI-131 decreased RANKL-induced osteoclast differentiation on the bone marrow derived macrophages cultures and reduced the resorbing activity of mature osteoclasts. WHI-131 suppressed the protein and mRNA expression of c-Fos and nuclear factor of activated T-cells cytoplasmic 1 (NFATc1) and down-regulated mRNA expression levels of TRAP, osteoclast-associated receptor (OSCAR), dendritic cell-specific transmembrane protein (DC-STAMP), osteoclast stimulatory transmembrane protein (OC-STAMP), d2 isoform of vacuolar H + ATPase V(0) domain (ATP6v0d2), and Cathepsin K. WHI-131 diminished the phosphorylation of Akt and degradation of I-kB. In addition, WHI-131 suppressed Ca 2+ oscillation by inhibiting phosphorylation of the c-Src-Btk-PLCg2 pathway. WHI-131 expression appeared to increase based on alkaline phosphate and alizarin red staining in relation to increased activity of the differentiation of primary osteoblast cells. WHI-131 increased the mRNA expression of genes related to osteoblast differentiation, including runt-related transcription factor 2 (Runx2), ALP, collagen type 1a (Col1a), osteocalcin (OCN), and OPN and induced the phosphorylation of Akt, p38, and Smad 1/5/8. Interestingly, WHI-131 had a notable anti-resorbing effects in the LPS-induced calvaria bone loss model in vivo . WHI-131 plays a dual role by inhibiting osteoclast differentiation and promoting osteoblast differentiation. Conclusions: Thus, WHI-131 may be a useful pharmacological agent that acts as a safe and effective dual-action therapeutic against osteoporosis, promoting robust bone growth while inhibiting resorption. Disclosure of Interest: None declared